Multidisciplinary parameterization study-based control-centric idea for hypersonic morphing vehicle. (July 2014) - Liu, Yanbin; Chen, Boyi; Xiao, Dibo; Zhang, Yong; Lu, Yuping
The design problems using multidisciplinary parameterization methods for a hypersonic morphing vehicle are investigated in this paper. First, the non-linear model of the hypersonic morphing vehicle in line with the parameterized process is established by combining with the different disciplines. Then, the waverider performances determined by the static and dynamic properties are discussed by application of the multidisciplinary design ideas. Afterwards, the optimal results considering the anticipated performance criteria are acquired by multidisciplinary optimization. Furthermore, the switching control system is designed for hypersonic morphing vehicle to implement the smooth morphing process and to guarantee the overall stability. Finally, the proposed methods are verified by a numerical example, and the resulting simulation shows that waveriding performance can be enhanced as the hypersonic vehicle is designed as a morphing shape.